Unique patterns of bereavement in HIV: implications for counselling. Issue 6 (December 1992) - Sherr, L; Hedge, B; Steinhart, K; Davey, T; Petrack, J
Abstract : OBJECTIVE–The aim of this study was to examine the nature and extent of bereavement problems in HIV + ve clients and the counselling input required. DESIGN–Ninety individuals referred consecutively for counselling by the medical teams after HIV diagnoses were included in the study. Specific bereavement data was gathered by each counsellor according to schedule and semi-structured interviews for all 90 subjects. These data were analysed in conjunction with medical referral letters. SETTING–HIV positive clients attending for treatment at an inner London Hospital. SUBJECTS–The subjects were 91% males and 9% females, mean age 33.82 years (SD 7.2, range 15 to 50 years, mode 28). 44.8% were diagnosed as HIV + ve (asymptomatic), 42.5% had an AIDS diagnosis and the remainder were coded as AIDS Related Complex or unclear. MAIN OUTCOME MEASURES–The subjects were monitored for the presence or absence of bereavement issues, the nature and extent of the reactions and counselling input. The occurrence of single and multiple bereavements was monitored, as were the relationship to the index patient and the health status of the bereaved. RESULTS–Bereavement was mentioned in 28.2% of referrals from medical practitioners yet 43.1% of the patients had been bereaved and used bereavement counselling. 43% spontaneously commenced the session with bereavement issues. They had lost 348 people (average of 12.9 deaths per person reporting). These were overwhelmingly due to AIDS with only 12 (5.6%) not HIV related. 65% linked the bereavement to their own death. Emotional reaction seemed to be independent of the relationship with the deceased but linked with the diagnosis status of the bereaved. CONCLUSION–The emotional consequences of a loss can be severe and long term. The advent of AIDS/HIV has revealed a wave of deaths in a population unused to facing traumatic loss to this extent. There are particular features surrounding AIDS and HIV infection which may differ dramatically from other sorts of loss and challenge previously held notions of bereavement such as the age of the clients, the fact that bereavements are often multiple the illness state of the bereaved person, the taboo surrounding AIDS which often presents barriers to wider social support and the catalogue of losses which any individual has to face. The frequency and high rate of bereavement, often not noted by referrers, suggests similarity with disaster literature in terms of counselling demand.